Internalisasi Nilai Kebhinekaan Melalui Permainan Tradisional Ase di Kabupaten Buton - Siti Misra Susanti; Hartati Hartati (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2026)
This study aims to examine the internalization of diversity values through the traditional Ase game among early childhood children in Buton Regency. The novelty of the study lies in its specific focus on the Ase game as a medium for instilling diversity values, differing from previous research that has generally explored traditional games within the broader context of character development. The study identifies key diversity values that emerge, including cooperation, tolerance, harmonious living, mutual assistance, solidarity, and empathy, while positioning the local wisdom of the Buton community as an empirical context that remains underexplored in early childhood education research. A descriptive qualitative approach was employed with ten children as research participants. Data were collected through observation, in-depth interviews, and documentation, and were analyzed using data reduction, data display, and verification procedures. The findings indicate that the traditional Ase game effectively internalizes diversity values through peer interactions, role distribution within teams, effective communication, and sportsmanship in accepting both victory and defeat. Therefore, the traditional Ase game has strong potential as a culturally based learning medium for instilling diversity values from an early age while simultaneously preserving local cultural heritage